FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELITUS TIPE 2 PADA PEKERJA PERUSAHAAN MINYAK DAN GAS DI PROVINSI RIAU - Annes Waren; Fahma Zainal; Zulhendry Zulhendry; Indrawan Indrawan (LPPM Universitas Abdurrab, 2023)
Background: Type 2 diabetes mellitus is a metabolic disorder characterized by an increase in blood sugar due to decreased insulin secretion by pancreatic beta cells. Data from the Pekanbaru City Health Office in 2019 showed that diabetes mellitus was ranked second in the 10 most common diseases. Every worker has potential hazards and risks in carrying out work that has an impact on occupational health problems. Working schedules can lead to unhealthy behaviors, such as eating, smoking, and exercising. Until now there is no data on type 2 diabetes mellitus among oil and gas workers at PT X in Riau province, but when the preliminary survey was conducted there were quite a number of workers with type 2 diabetes mellitus whose incidence rate of disease 2 was not known in the company. Objectives : it is necessary to carry out prevention and control efforts by looking at the risk factors that affect the disease. Methods: This research is a descriptive observational study with a cross- sectional study design and using the chi-square test Results: he results of this study indicate that there are 179 (6.8%) workers who are affected by the incidence of type 2 diabetes mellitus and the variable associated with the incidence of type 2 diabetes mellitus in workers at the oil and gas company PT X in Riau province is age (p=0.00 and PR=5.286), BMI (P=0.00 and PR=1.875), gender (P=0.047 and PR=1.714), type of work (P=0.003 and PR=0.631), and variables that are not related are activity physical (P = 0.486). Conclusion: There is a significant relationship between age, BMI, gender and type of work with the incidence of type 2 diabetes mellitus in workers at the oil and gas company PT X in Riau province. Keyword : Diabetes mellitus type 2, workers oil and gas